Genetic Analyses of sea urchin in Malaysian Borneo - Nursyuhaida, Md Shahid (2013)
Echinoidea is the well known class in Phylum Echinodermata, with over 900 extant species. They play significant roles in maintaining the health of coral reef ecosystems and the associated organisms. Genus Diadema (Echinoidea: Diadematidae) have been reported to be the most widespread and ecologically important shallow water genera of tropical sea urchins. Distinctions in their distributions and ecology among species of genus Diadema, are complicated to elucidate due to complexity in making reliable identifications. Genus Diadema had involved in many debates, particularly on the specific status of the sympatric species, Diadema setosum and Diadema savignyi. Therefore, phylogenetic relationships of Genus Diadema in Malaysian Borneo have been conducted using 16S rRNA gene analysis. Monophyletic clade of genus Diadema with respect to the outgroup was revealed with significant bootstrap support. Two monophyletic clades with deep split separating D. setosum (Clade I) and D. savignyi (Clade II) were observed, with significant bootstrap support and high genetic variation recorded (9.85%). The results suggested that D. setosum and D. savignyi are two distinct entities based on phylogenetic analysis and unique morphological characteristics observed. The results also suggest that D. setosum and D. savignyi are sympatric species based on their distribution and overlapping ranges in Malaysian Borneo. Genetic structure and extent of variation among D. setosum from Malaysian Borneo (Satang Island, Sarawak; Mantanani Island, Sabah; Kudat, Sabah and Larapan Tengah, Sabah) were later conducted using 16S rRNA gene analysis to test whether the population of D. setosum in Malaysian Borneo is panmictic or structured. Lack of a significant relationship between net nucleotide divergences (Da) and geographic distance was revealed indicates no associations between genetic and geography of D. setosum in Malaysian Borneo. No distinct geographical clades could be observed among D. setosum populations and minimum-spanning network (MSN) revealed sharing of haplotypes among populations. High number of migrants per generation (Nm = 2.14 to 17.20) with low nucleotide subdivision (Nst = 0.03 to 0.19) and estimate of population subdivision (FST = 0.03 to 0.19) were recorded, except for Mantanani Island population. Mantanani Island population showed low level of gene flow (Nm = 0.13 to 0.69) and significant genetic differentiation ΦST values suggesting slight genetic isolation and subdivision from Larapan Tengah and Kudat populations. Gene flow occurrence among D. setosum populations suggested population expansion and that D. setosum population in Malaysian Borneo is panmictic. D. setosum as a highly dispersive species that possessed long planktonic stage might explain the gene flow occurrence among populations which further facilitated by historical events, prevailing surface current and impact of ballast water. Whereas, slight genetic isolation of Mantanani Island population occurred due to dispersal restriction of D. setosum larvae influenced by the historical events on the isolation of South China Sea from Sulu- Celebes Sea, water flow restrictions in the connecting straits, prevailing South China Sea Southwest monsoon and the formation of gyres off the Borneo coast. All findings from this study are based on limited samples thus future studies should involve more specimens collected from a wider geographical area in order to further understand the genetic structure and phylogenetic relationships of sea urchin in Malaysian Borneo.